Reconseptualising critical thinking as a linguistic practice in a Media ESP programme - Hadjiconstantinou, Stavroulla (My University, 2022)
The primary goal of this research study is to explore pedagogies that develop language through practices of critical thinking (CT). In recognition of the importance of CT in education, myside bias – a CT construct from cognitive psychology (Stanovich & West, 2007; Toplak & Stanovich, 2003) – is explored for its potential as a linguistic practice in the creation of a framework enhancing the development of language through the construction of meaning (Halliday & Hasan 1989). At the same time, research in critical pedagogy highlights the effectiveness of raising learners’ critical awareness through language in support of language learning (Luke, 2004; Morgan, 2009). Situated in an English for Specific Purposes context, the design in this study derives from critical analysis of instances of myside bias identified in the language used in media texts. The design develops through an iterative process of data collection and analysis completed in a four-stage intervention informed by design-based research (DBR) methodology. The intervention includes three cycles of implementation, evaluation, and refinement of the design, which involves learners in instructional practices of identification, reconstruction, and critical discussion of the functions of specific linguistic resources in support of linguistic and critical thinking development. Results highlight the effectiveness of the design in using a framework based on the construct of myside bias to create a purpose for engaging with language in critical ways. Engaging with language through repetition of critical thinking practices, in which the use of functional metalanguage facilitates students’ understanding of the potential of language in conveying opinion, develops learners’ ability to appropriate and use these practices in critically approaching texts more independently. The design and principles developed in this study have larger implications for theory and practice, indicating a potential for future applications in other language contexts.